THE OPPORTUNITIES AND CHALLENGES OF MAKASSAR GOVERNMENT TOWARDS IMPROVING SERVICES FOR PUBLIC COMPLAINTS BASED ON E-GOVERNMENT - Riska Sarofah (Jurnal Ilmiah Wahana Bhakti Praja, 2017)
The development of e-Government in Indonesia is increasingly growing in an attempt to give the public services based on ICT (Information and Communication Technologies). E-Government policy is in accordance with the Instructions of the President of Republic Indonesia number 3 in 2003 about policy and national strategy for the development of e-Government in an effort to facilitate the interests and demands of the society. The development of e-Government needs to be planned and implemented through measureable goals for public service in Indonesia. e-Government is one of the principal dimensions of the system of state administration. The implementation of the concept of information technology by the government to make the state administration system to be more effective, efficient, and transparent. One of the city in Indonesia which try to implement e-Government in improving public service is Makassar. This study aims to examine the opportunities and challenges of Makassar government towards improving services for public complaints based on e-Government. One of the strategy and innovation is undertaken by the Makassar government by way of creating e-aspiration. To examine the opportunities and challenges of Makassar Government to improve services for public complaints which based e-Government, we conducted literature study on relevant with previous research and statistical data. Makassar government has shown its enthusiasm surrounding the use of information and technology in many occasions. However, the use of e-aspiration by the government and society are still limited. Therefore, despite that e-aspiration may bring greater benefit in improving good governance. However, this issue of e-aspiration remains difficult in Makassar and in general for Indonesia due to many challenges and obstacles on several dimensions. In consideration of the opportunities and challenges of e-Government is also to be seen from the aspect of society participation in the use of technology and responsiveness of the Government in the development of e-Government services.